Pembangunan Iman dan Pembangunan Fisik Jemaat Terpencil Sebagai Wujud Pelayanan Holistik - Doni Ariani Leowandri Liu; Kristiani E.Y.M. Afi; Fenetson Pairikas; Simon Kesse; Orista Y.D Mone; Melti M. Fomeni; Hita Bolo; Yetni Tafuli (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
Based on the results of the interviews, information was found that the building of the congregation's faith and the physical construction of the church were issues faced by the GMIT Efata Oetfo congregation. The building of the faith of the congregation in question is related to the ministry, among others: 1). The absence of categorical worship of the fathers; 2). The absence of youth categorical worship; 3). Mothers are less active in categorical worship. The physical development in question is related to the completion of the construction of the church building, in this case the installation of ceramics that has not been carried out. Responding to these issues, the PKM implementation team conducted a needs analysis and found a solution to the problem, namely by conducting seminars and installing ceramics. The objectives to be achieved in this PKM activity are: 1). PKM participants can gain some knowledge as a form of education that can open their horizons of thinking about the importance of building faith through worship in service. The participants were also able to gain some knowledge about the role of the church in the economic empowerment of the congregation as a strategic way to increase the income of the congregation; 2). The church building of the GMIT Efata Oetfo congregation is progressing. The method of implementing the activity consists of several stages, namely: 1). Welcoming and reception of the congregation; 2). Opening; 3) Implementation of Seminar Activities; 4). Implementation of Ceramic Installation Activities; 5). Closing; 6). Activity Evaluation.